Peasants, Potatoes and Pesticides: Heterogeneity in the Context of Agricultural Modernization in the Highland Andes of Ecuador - Paredes Chauca, Myriam (2010)
The Province of Carchi in the highland Andes of northern Ecuador has been the focus of extensive research on the dynamics of health, environment and productivity since the early nineties. A collection of multidisciplinary research, summarized in Crissman et al (1998) and updated in Yanggen et al (2003a), describes an intensive potato-pasture system that is highly productive (2-3 times the national average in terms of yield per area), but one that generates serious health and environmental problems. Research has found that the use of pesticides leads to chronic toxicity, which affects approximately two-thirds of the rural population. The introduction of mechanized tillage and the disk plough has resulted in the degradation of soils at an annual rate of between 80 and 120 tonnes per hectare. Price fluctuations result in farmers losing money on about 36 percent of their crops.